An Analysis Of Feminist Thoughts Of Life’s Struggle Presented In The Movie “Little Woman (2019)” - Rara Pramudhita Nurani Putri; Abdillah Nugroho (Eduvest - Journal of Universal Studies, 2024)
Modern women frequently encounter challenges in their perspectives on life's struggle, such as focusing on social expectations of women, experiencing a lack of spiritual support in relationships, and facing a disconnection between education, job, and marriage, which hinders their pursuit of an ideal partnership. This research examines the life of education, marriage experiences, ideas, and inspirations of Jo March in the movie "Little Women" to face the challenges of women in their views on life. The data was collected from two sources the movie Little Women (2019) and other sources of literature. The result revealed that the feminist thought of life struggle found in several aspects, such as the struggle for freedom, the struggle for education, and the Struggle for happiness. These struggles were fueled by the unfair treatment of women, who were subjected to a patriarchal society that taught them they were less important than men and should adhere to men's decisions. The societal expectation that women's happiness was contingent upon male support further limited their pursuit of independence. In this era, the concept of freedom seemed distant and unattainable for women, highlighting the pervasive and systemic barriers they faced.